Workplace Harassment and Attitudes towards LGBT People: Differences across Human Service Occupations in South Florida - Daniel Sheridan; Joseph Zolobczuk; Kiet Huynh; Debbiesiu L. Lee (University of North Florida, 2017)
Research documents that discrimination and harassment directed toward lesbian, gay, bisexual, and transgender (LGBT) individuals are ongoing and prevalent in the workplaces in the United States. However, no studies have identified the specific occupations wherein LGBT-discrimination and harassment are most severe. Furthermore, no study has examined how prepared and comfortable employees feel in addressing discriminatory situations. Utilizing a dataset comprised of 1,691 participants, in this exploratory study we sought to identify whether differences in workplace environment toward LGBT individuals existed across four human service occupations (mental health, medicine, education, and public and private government-related non-profit community organizations). We found that education professionals reported the highest incidences of verbal and physical harassment directed toward LGBT individuals. Education professionals also reported feeling least prepared to handle sexual orientation and gender- related issues despite being most likely to speak-up against sexual orientation and gender-identity bullying. Medical professionals reported receiving the least amount of training on LGBT-related contact. Differences across race/ethnicity and gender regarding discriminatory LGBT attitudes and environment were also found. Our results offer important implications for researchers and workplace equality advocates that seek to foster affirming workplace environments for sexual and gender minorities.